Psikoterapi Sufistik dalam Pengobatan Reiki pada Masa Pandemi Covid-19 - M. Agus Wahyudi; Syamsul Bakri (Syifa al-Qulub, 2021)
Reiki Sufism is a spiritual practice and healing of physical and psychological ailments through Sufism values using the Reiki method. Sufism is a scientific field in Islam that concentrates on the inner realm (esoteric). Meanwhile, reiki is a healing technique from Japan that utilizes the energy of the universe or is called Divine energy. Seeing the current conditions in the world that is being hit by the Covid-19 outbreak, the behavior shown by the community has changed. This incident not only had an impact on the health sector but also had an impact on the religious sector. So it is necessary to do research on how to mitigate or handle the Covid-19 outbreak. The method in this study uses a qualitative descriptive approach and literature study with the formulation of the problem of how the contribution of Reiki Sufism in the face of the Covid-19 outbreak. The purpose of this research is to describe Reiki Sufism techniques in breaking the chain of the spread of the Covid-19 outbreak. The results of this research are the practice of self-healing, uzlah (self-isolation), khalwat (solitude), and meditation dhikr that can be used as alternatives in breaking the chain of the spread of the Covid-19 outbreak and making individuals able to adapt to the pandemic.